Characteristics of Inescapable Hyperreality in The Four Stages of Simulacra in The Truman Show Movie - Nuraini, Sheila; Netra, I Made (ENGLISH JOURNAL OF INDRAGIRI, 2026)
This study explores the hyperreality in literature by analyzing “The Truman Show” movie that was first aired in 1998. Hyperreality can be understood as the collapsed boundaries between reality and simulation. It is created through the building blocks called simulacra. Using Baudrillard (1981)’s theory of hyperreality, the research examines what characteritics of inescapable hyperreality are pictured in each orders of the four stages of simulacra in the movie. This study applied qualitative approach to analyze the characteristics of inescapable hyperreality in the four stages of simulacra, which includes blurring boundaries, media influence, absence of originality, and idealized reality. This study found the first order of simulacra represent the characteristics of blurring boundaries and idealized reality. The second order of simulacra represent the characteristics of blurring boundaries, media influence, and idealized realities. The third order of simulacra represent the characteristic of blurring boundaries, media influence, and the absence of originality. The fourth order of simulacra represent the characteristic of blurring boundaries, media influence, absence of originality, and idealized reality. This study aims to fill the gap from previous studies to provide a fresh perspective on how language constructs and reinforces hyperreality by focusing on the verbal elements.